Attitudes of Modern Youth to the Innovative Activities: Based on the Materials of Sociological Research - E. E. Ushenkov (Дискурс)
Introduction. Orientation of the Russian to innovative way of development requires the provision of the state of human resources – qualified specialists with a certain set of qualities, skills and competencies. Researchers studying the matter, concluded that such a resource is the youth as the most active and creative social and demographic groups. Important components of the innovative potential of young people are the open mindedness, self-interest and involvement in innovative processes.The author carries out a case study, the aim of which is to study the attitudes and engagement of young people of the Ivanovo region in innovation activities.Methodology and sources. The methodological basis of this work is the sociological researches conducted by the author. The subject of these studies were representatives of youth of the Ivanovo region in age from 14 to 30 years. During the research, several sub-groups divided the youth group: senior pupils, students and representatives of working youth. Sampling error does not exceed 5 %, for a given level of significance of 95 %.Results and discussion. The study showed that only half of the youth in the region would like to take part in innovative activities. At the same time over the past 3 years, about 44 % of young people have taken part in some form of innovation activity. Revealed that innovative practices are most common for pupils and students. Young people engaged in professional activities in more than half of the cases had no experience of participation in innovative activities.Conclusion. The results of the author of sociological studies show varying degrees of readiness of youth to innovative activities. Pupils and students largely than older youth, interested in innovative practices, due to its involvement in these processes through the use of new educational technologies. The interest of working youth is determined by the content of the profession.